A Luminescent Hypercrosslinked Conjugated Microporous Polymer for Efficient Removal and Detection of Mercury Ions. Issue 17 (18th June 2015) - Xiang, Lu; Zhu, Yunlong; Gu, Shuai; Chen, Dongyang; Fu, Xian; Zhang, Yindong; Yu, Guipeng; Pan, Chunyue; Hu, Yuehua
<x xml:space="preserve">Abstract</x> A hypercrosslinked conjugated microporous polymer (HCMP‐1) with a robustly efficient absorption and highly specific sensitivity to mercury ions (Hg2+) is synthesized in a one‐step Friedel–Crafts alkylation of cost‐effective 2, 4, 6‐trichloro‐1, 3, 5‐triazine and dibenzofuran in 1, 2‐dichloroethane. HCMP‐1 has a moderate Brunauer–Emmett–Teller specific surface (432 m2 g−1), but it displays a high adsorption affinity (604 mg g−1) and excellent trace efficiency for Hg2+. The π–π* electronic transition among the aromatic heterocyclic rings endows HCMP‐1 a strong fluorescent property and the fluorescence is obviously weakened after Hg2+ uptake, which makes the hypercrosslinked conjugated microporous polymer a promising fluorescent probe for Hg2+ detection, owning a super‐high sensitivity (detection limit 5 × 10−8 mol L−1).